2019
DOI: 10.1620/tjem.247.251
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Oral Self-Care on Pneumonia Death among the Elderly with Tooth Loss: The Ohsaki Cohort 2006 Study

Abstract: Tooth loss is a risk factor for pneumonia mortality, but it is unclear whether oral care negates excess mortality due to pneumonia among community-dwelling elderly with tooth loss. The purpose of this study was to examine the influence of oral care on the association between the number of remaining teeth and the risk of pneumonia death. We analyzed for 18,098 individuals (aged ≥ 65 years) participating in a prospective cohort study. In a 2006 baseline survey, the following data were collected: the number of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In the HABC study, partial and complete tooth loss were associated with increased respiratory mortality after adjustment for confounders. This finding was supported by two previous studies in older Japanese populations 6 , 50 . It has been suggested that eating difficulties along with tooth loss resulted in increased risk of respiratory mortality 6 .…”
Section: Discussionsupporting
confidence: 89%
“…In the HABC study, partial and complete tooth loss were associated with increased respiratory mortality after adjustment for confounders. This finding was supported by two previous studies in older Japanese populations 6 , 50 . It has been suggested that eating difficulties along with tooth loss resulted in increased risk of respiratory mortality 6 .…”
Section: Discussionsupporting
confidence: 89%
“…The number of residual teeth is clearly paramount to mastication. A study conducted in Japan demonstrated that the retention of more than 20 teeth is necessary for effective masticatory ability [37]. It is reasonable to suppose that low masticatory ability in older people caused by the loss of multiple teeth affects dietary choices and therefore reduces quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Indisputably, the number of residual teeth is paramount to mastication. In Japan, a study demonstrated that retaining more than 20 teeth is necessary for retention of effective masticatory ability (37). With multiple tooth loss in older people, it is not unreasonable to expect that low masticatory ability may affect dietary choices and may therefore reducing quality of life.…”
Section: Discussionmentioning
confidence: 99%